2022
DOI: 10.1002/app.53521
|View full text |Cite
|
Sign up to set email alerts
|

Strong and high void fraction PP/CNS nanocomposite foams fabricated by core‐back foam injection molding

Abstract: Polypropylene/carbon nanostructure (PP/CNS) nanocomposite foams with a void fraction as high as 78% were successfully prepared by foam injection molding (FIM) with core-back operation. Rheological curves and differential scanning calorimetry results showed that the added CNS significantly improved the melt strength and accelerated the crystallization process of PP, respectively. A high mold temperature was applied to overcome the adverse effect of CNS, which had a high thermal conductivity and went against the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Consequently, the EMI SE produced comparatively higher results than the un-foamed composite counterpart (around 37 dB, almost 30% higher than the non-foamed composite). A similar injection molding-based foaming process (specifically, the core-back injection process) was used by Wang and co-workers [ 12 ] to prepare lightweight polypropylene (PP)-carbon nanosheets (CNS) and nanocomposite foams with microcellular structures. In this work, the authors showed that it was possible to obtain foams with higher specific flexural modulus values than that of their respective un-foamed injection-molded counterparts; hence, foams show great potential as EMI shields for sensor-based applications.…”
Section: Microcellular Foaming For Emi Shielding Applicationsmentioning
confidence: 99%
“…Consequently, the EMI SE produced comparatively higher results than the un-foamed composite counterpart (around 37 dB, almost 30% higher than the non-foamed composite). A similar injection molding-based foaming process (specifically, the core-back injection process) was used by Wang and co-workers [ 12 ] to prepare lightweight polypropylene (PP)-carbon nanosheets (CNS) and nanocomposite foams with microcellular structures. In this work, the authors showed that it was possible to obtain foams with higher specific flexural modulus values than that of their respective un-foamed injection-molded counterparts; hence, foams show great potential as EMI shields for sensor-based applications.…”
Section: Microcellular Foaming For Emi Shielding Applicationsmentioning
confidence: 99%
“…As mentioned before, as the combination of CF addition and chemical foaming led to foams with more uniform smaller-sized cellular structures, EMI SE resulted comparatively higher than the unfoamed composite counterpart (almost 37 dB, almost 30% higher than the non-foamed composite). A similar injection molding-based foaming process, more specifically core-back injection, was used by Wang and co-workers [28] to prepare lightweight polypropylene (PP)-carbon nanosheets (CNS) nanocomposite foams having a microcellular structure. In this work, the authors showed that it was possible to obtain foams having higher specific flexural modulus values than that of their respective unfoamed injection-molded counterparts, hence foams showing great potential as EMI shields for sensor applications.…”
Section: Other Microcellular Foaming Technologiesmentioning
confidence: 99%